Genetic diversity of begomoviruses infecting tomato from são paulo midle-west - Cotrim, Marco Antonio de Andrade [UNESP]; Krause-Sakate, Renate [UNESP]; Narita, Nobuioshi [UNESP]; Zerbini, Francisco Murilo; Pavan, Marcelo Agenor [UNESP] (My University, 2007)
The genetic variability of viruses belonging to the Begomovirus genus infecting tomatoes (Lycopersicon esculentum Mill) on field areas from the mid-western region of São Paulo state was evaluated. From January 2003 to February 2004, one hundred and sixty-six tomato samples were collected and the presence of begomoviruses detected on 60% of the samples by PCR, using universal primers for the genus. Direct sequencing of PCR products of 16 selected samples indicated the possible presence of Tomato severe rugose virus (ToSRV), Sida mottle virus (SiMoV-[BR]) and the tentative species Tomato yellow vein streak virus (ToYVSV-[BR]). A possible new species of begomovirus was detected in two samples. The presence of ToSRV and SiMoV had not yet been reported in São Paulo state. These results indicate the existence of genetic diversity of begomovirus species infecting tomatoes in this area, and serve as an alert for breeders searching for resistance against this important group of pathogens.
Diversidade genética de begomovírus em cultivos de tomateiro no centro-oeste paulista
Keywords: Additional geminivirus; Variability